Utilization of Biotechnological Methods for Enhancing Yield and Quality of Spirulina Production - Tetiana Korobovska (Progress in Science, 2024)
Spirulina (Arthrospira platensis) is recognized as one of the most promising sources of protein and a rich repository of bioactive compounds. To enhance both the yield and quality of spirulina production, various biotechnological approaches and methods have been employed. One of the key aspects of spirulina cultivation lies in optimizing the growth conditions. Biotechnological methods enable the creation of optimal conditions for the growth and development of the microorganism, including temperature control, illumination, pH levels, and CO2 concentration. The cultivation of spirulina using biotechnological methods offers several advantages over conventional approaches. Bioreactor systems provide precise control over environmental factors such as temperature, light intensity, pH, and nutrient availability, resulting in optimized growth conditions for spirulina. Photobioreactors, in particular, offer advantages in terms of scalability, productivity, and sterility, making them a preferred choice for large-scale spirulina cultivation.